Audience Engagement With Electric, Hybrid and Internal Combustion Vehicle Content Among Automotive Creators - Kuchta, Martin; Učeň, Patrik (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The transition from internal combustion engine (ICE) vehicles toward hybrid and fully electric vehicles (EVs) is reshaping both the automotive industry and audience interest in mobility technologies within digital media environments. This study investigates whether audience engagement differs between online review videos focused on electric, hybrid, and internal combustion vehicles. The analysis is based on 75 videos published by five established European automotive content creators, with engagement compared using quantifiable platform metrics such as views, likes, comments, video duration, publication date, and channel subscriber counts. The study combines descriptive analysis with non-parametric statistical testing, including Kruskal-Wallis tests, Spearman correlation analysis, and the Mann-Whitney U test. The descriptive results indicate that EV videos achieved the highest average normalized view performance and comment intensity; however, statistically significant differences between powertrain categories were not confirmed. The findings further suggest that video length and the distinction between reach and engagement intensity represent important factors in evaluating automotive content performance. The study contributes to a better understanding of digital audience engagement in automotive review content and provides exploratory implications for automotive brands and content creators seeking to optimize communication strategies across different powertrain categories.